Exploring Multimodality in a Student Self-Directed Learning Unit to Facilitate Differentiated Learning - Ramadhani, Izza Aulia; Fauziana, Erni; Rakhmawati (ICONELT, 2024)
This study aims to explore multimodal elements in a Student Self-Directed Learning Unit (UKBM) to facilitate differentiated learning. Using a qualitative research design to explore various multimodal elements—such as text, images, audio, video, and interactive elements—and analyze how those elements can facilitate different student needs. It was found that multimodal elements used in a Student Self-Directed Learning Unit (UKBM) can facilitate different learning styles, readiness levels, and interests of students. Overall, this study focuses on the use of multimodal elements in a Student Self-Directed Learning Unit (UKBM) to accommodate different student needs in learning English.